Developing the Character of Elementary School Students Through Values-Based Leadership - Yoyo Zakaria Ansori; Dede Salim Nahdi; Anda Juanda; Erik Santoso (AL-ISHLAH: Jurnal Pendidikan, 2024)
Formal educational institutions play a pivotal role in shaping student character, which extends beyond individual development to influence the broader educational environment. Building strong character is essential for preparing students to navigate societal trends and challenges. School leadership is a critical determinant of the success or failure of character development initiatives. This study employed a qualitative approach with a descriptive research design to explore the role of leadership in character development. The research was conducted at an integrated Islamic school in Majalengka, involving principals and teachers as respondents. Data collection focused on observing leadership practices and their impact on student character formation. The findings demonstrate that values-based leadership significantly contributes to developing student character. Key leadership values identified include leading by example, fostering kinship, promoting cooperation, and practicing visionary leadership. These values collectively create an environment that supports character education and enhances the school’s role in preparing students for future challenges. The results emphasize that effective leadership is foundational to embedding character-building practices in formal education. Values-based leadership not only strengthens student character but also fosters a positive and collaborative school culture. These insights align with the need for leadership models that prioritize ethical and relational practices. This study highlights the importance of values-based leadership in character development within schools. Future research should explore its application in diverse educational contexts to refine strategies for cultivating ethical and responsible future generations.